Regulation by Dietary Carbohydrates of Intermediary Metabolism in Liver and Muscle of Two Isogenic Lines of Rainbow Trout - Song, Xuerong; Marandel, Lucie; Skiba-Cassy, Sandrine; Corraze, Geneviève; Dupont-Nivet, Mathilde; Quillet, Edwige; Geurden, Inge; Panserat, Stephane (Frontiers in Physiology, 2018)
Rainbow trout (Oncorhynchus mykiss) is recognized as a typical “glucose-intolerant” fish, and the limits of dietary carbohydrate utilization have been investigated for many years. In this study, the objective was to test the molecular effects of dietary carbohydrates on intermediary metabolism in two major metabolic tissues, liver and muscle. One more objective was also to study if the response to carbohydrate intake depended on the genetic background. We fed two isogenic lines of rainbow trout (named A22h and N38h) with high carbohydrate diet (carbohydrate, 22.9%) or low carbohydrate diet (carbohydrate, 3.6%) for 12 weeks. Carbohydrates were associated with higher feed utilization owned to the protein-sparing effect, and also made a benefit fish growth, but atypical regulation of glycolysis and gluconeogenesis in liver and with an absence of induction of hk and glut4, the first two steps of glucose use in muscle. Regarding the effects of carbohydrates on other metabolism than the glucose one, we observed an increased, at a molecular level, of hepatic lipid and cholesterol biosynthesis, fatty acid oxidation and mitochondrial energy metabolism. Genetic variability (revealed by the differences among the two isogenic lines) was observed for some metabolic genes especially for the EPA and DHA biosynthetic capacity. Finally, our study demonstrates that dietary carbohydrate not only affect glucose metabolism but also strongly impact the lipid and energy metabolism in liver and muscle of trout.